Letter (copy) - Middleton, J. S. ; Lindsay, H. Scott; Citrine, Walter, 1887-1983
1936-10-22 DR. October 22nd, 1936. Rt. Hon. Anthony Eden, M.C., M.P. The Foreign Office, Downing Street, S.W.1. Dear Minister, The National Council of Labour at its meeting yesterday, viewed with grave concern the time which has elapsed since the Spanish Non-Intervention Committee undertook to investigate the charges of violation of the Non-Intervention Agreement which had been submitted to it. The Council had before it a statement from Senor Del Vayo, a copy of which is attached, and it came to the conclusion that if there is substance in but a proportion of the allegations which have been published from time to time, the Non-Intervention Agreement has been violated. The Council took the view that His Majesty's Government and other Governments must have at their disposal, through their consular officers and other agents, information regarding the observance or non-observance of the Non-Intervention Agreement, and is of the opinion that there has been undue delay in arriving at a conclusion as to the truth or otherwise of the allegations which have been made. The Council calls upon the British Government to take all possible steps to expedite the findings of the investigation and to insist upon full a public statement of the results at the earliest possible moment. Yours sincerely, ON BEHALF OF THE NATIONAL COUNCIL OF LABOUR Walter Citrine Secretary, General Council of thE Trades Union Congress, J.S. Middleton Secretary, Executive Committee of the Labour Party H. Scott Lindsay Secretary, Parliamentary Labour Party 292/946/10/75